Feedback Inhibition of the Unfolded Protein Response by GADD34-Mediated Dephosphorylation of eIF2α - Novoa, Isabel (The Rockefeller University Press, 2001)
Phosphorylation of the α subunit of eukaryotic translation initiation factor 2 (eIF2α) on serine 51 integrates general translation repression with activation of stress-inducible genes such as ATF4, CHOP, and BiP in the unfolded protein response. We sought to identify new genes active in this phospho-eIF2α–dependent signaling pathway by screening a library of recombinant retroviruses for clones that inhibit the expression of a CHOP::GFP reporter. A retrovirus encoding the COOH terminus of growth arrest and DNA damage gene (GADD)34, also known as MYD116 (Fornace, A.J., D.W. Neibert, M.C. Hollander, J.D. Luethy, M. Papathanasiou, J. Fragoli, and N.J. Holbrook. 1989. Mol. Cell. Biol. 9:4196–4203; Lord K.A., B. Hoffman-Lieberman, and D.A. Lieberman. 1990. Nucleic Acid Res. 18:2823), was isolated and found to attenuate CHOP (also known as GADD153) activation by both protein malfolding in the endoplasmic reticulum, and amino acid deprivation. Despite normal activity of the cognate stress-inducible eIF2α kinases PERK (also known as PEK) and GCN2, phospho-eIF2α levels were markedly diminished in GADD34-overexpressing cells. GADD34 formed a complex with the catalytic subunit of protein phosphatase 1 (PP1c) that specifically promoted the dephosphorylation of eIF2α in vitro. Mutations that interfered with the interaction with PP1c prevented the dephosphorylation of eIF2α and blocked attenuation of CHOP by GADD34. Expression of GADD34 is stress dependent, and was absent in PERK(−)/− and GCN2(−)/− cells. These findings implicate GADD34-mediated dephosphorylation of eIF2α in a negative feedback loop that inhibits stress-induced gene expression, and that might promote recovery from translational inhibition in the unfolded protein response.